Vaccination with post-translational modified, homocitrullinated peptides induces CD8 T-cell responses that mediate antitumor immunity - Ian Pike; Victoria A Brentville; Peter Symonds; Katherine W Cook; Lindy G Durrant; Sabaria Shah; Samantha J Paston; Juliane Weißer; Anne Skinner; Abdullah Al Omari (Journal for ImmunoTherapy of Cancer, 2023)
Background Post-translational modification of proteins has the potential to alter the ability of T cells to recognize major histocompatibility complex (MHC) class -I and class-II restricted antigens, thereby resulting in altered immune responses. One such modification is carbamylation (homocitrullination) that results in the formation of homocitrulline (Hcit) residues in a non-enzymatic reaction of cyanate with the lysine residues in the polypeptide chain. Homocitrullination occurs in the tumor microenvironment and CD4-mediated immune responses to Hcit epitopes can target stressed tumor cells and provide a potent antitumor response in mouse models.Methods Homocitrullinated peptides were identified and assessed in vitro for HLA-A2 binding and in vivo in human leukocyte antigen (HLA) transgenic mouse models for immunogenicity. CD8 responses were assessed in vitro for cytotoxicity and in vivo tumor therapy. Human tumor samples were analyzed by targeted mass spectrometry for presence of homocitrullinated peptides.Results Homocitrullinated peptides from aldolase and cytokeratin were identified, that stimulated CD8-mediated responses in vivo. Modified peptides showed enhanced binding to HLA-A2 compared with the native sequences and immunization of HLA-A2 transgenic mice generated high avidity modification specific CD8 responses that killed peptide expressing target cells. Importantly, in vivo the homocitrullinated aldolase specific response was associated with efficient CD8 dependent antitumor therapy of the aggressive murine B16 tumor model indicating that this epitope is naturally presented in the tumor. In addition, the homocitrullinated aldolase epitope was also detected in human tumor samples.Conclusion This is the first evidence that homocitrullinated peptides can be processed and presented via MHC-I and targeted for tumor therapy. Thus, Hcit-specific CD8 T-cell responses have potential in the development of future anticancer therapy.